Relatório de Estágio Profissional "A aprendizagem dentro da escola do Cerco: Passagem da teoria para a prática" - Cátia Rafaela Pinto Mota (2019)
Report of Internship in obtaining the 2nd Cycle of Studies leading to the Master's Degree in Basic and Secondary Education of the Faculty of Sport of the University of Porto. As a trainee, I completed my professional internship at the Basic and Secondary School of Cerco, with the objective of continuing the learning of the performance of all functions relative to the teaching activity, inserted in a trainee nucleus, composed of three elements, a teacher cooperative member of the school staff and a faculty advisor. The purpose of this work is to reflect, analyze and review my entire course in school, which allowed me to develop and improve some of my abilities as a teacher, thus allowing me to increase both personally and professionally in the various areas of intervention in the school community. This report is distinguished by different chapters: Introduction; a Personal dimension where I portray my life path up to the completion of the Professional Internship; the Framework of Professional Practice where it is inserted, the teaching practice and the characterization of the trainees and students; as well as a summary of the activities carried out throughout the school year and finally the Conclusion, where she describes my entire career as a trainee teacher, as well as my future motivations and expectations. I'm thinking of putting together a study based on the theme: "The Combat of Anxiety through Physical Activity